Integrated chitinozoan, conodont, and graptolite biostratigraphy from the upper part of the Cape Cormorant Formation (Middle Ordovician), western Newfoundland - ALBANI, ROBERTO; BAGNOLI, GABRIELLA; MALETZ J.; STOUGE S. (Canadian Journal of Earth Sciences, 2001)
The Cape Cormorant Formation of the Table Head Group exposed on the Port au Port Peninsula, western Newfoundland, is composed of dark-brown to black shales with interbeds of thin calcareous silty and sandy distal turbidites. Distinctive carbonate conglomerates and breccias derived from the foundering shelf are occasionally found in the formation. The sediments accumulated in the foreland basin formed during the early stage of the Taconic orogeny. The faunas from the upper part of the Cape Cormorant Formation include graptolites, conodonts, and chitinozoans. The graptolites are well preserved, but are of low diversity and are referred to the Darriwil Pterograptus elegans Zone. Conodonts recorded from the distal turbidites are rare and fragmented. The faunas include taxa that are known from the St. George and Table Head groups. The conodont fauna is tentatively assigned to the Histiodella kristinae Phylozone and to the younger, unzoned interval. The chitinozoans are well preserved and the yield is high. The fauna is assigned to the Cyathochitina jenkinsi Zone and to an undefined interval. The abundance and diversity of the chitinozoan assemblages display a cyclic pattern, which is related to changes of the oceanic watermass in the foreland basin. The new chitinozoan species Belonechitina nevillensis n. sp., Belonechitina uniformipunctata n. sp., and Cyathochitina cormorani n. sp. are described.